ANALISIS PENGARUH WORKING CAPITAL DALAM PROFITABILITAS - Nathania, Patricia -; Putra, Wilxen Sanjaya; Pricilya, Zuliet -; Meiden, Carmel - (Makro Jurnal Manajemen Dan Kewirausahaan, 2023)
The research was conducted with the hope of knowing how much influence working capital has on the profitability of a company. Working Capital is an investment owned by a company that is kept with the aim of being used to finance current assets. In research, one of the many theoretical foundations used in this study, the theory used is attribution theory. The research was conducted using a literature study method where after selecting the data in accordance with the applicable criteria, the number of samples obtained was 30 samples where the data obtained were data from the 2010-2022 period, sourced from various countries. In this research, the emphasis is on the use of research methods used by various sample literatures that will be used as research conclusions. Based on the results of the study, it shows that the biggest influence of working capital on profitability is the Cash Ratio and shows that working capital has a significant effect on profitability.